2003
DOI: 10.1093/hmg/ddg007
|View full text |Cite
|
Sign up to set email alerts
|

Results of a high-resolution genome screen of 437 Alzheimer's Disease families

Abstract: Alzheimer's disease (AD) is a devastating neurodegenerative disorder of late life with complex inheritance. Mutations in three known genes lead to the rare early-onset autosomal dominant form of AD, while a common polymorphism (epsilon 4) in the gene encoding apolipoprotein E (APOE ) is a risk factor for more typical late-onset (>60 years) AD. A recent study concluded that there are up to four additional genes with an equal or greater contribution to the disease. We performed a 9 cM genome screen of 437 famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
194
3
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(223 citation statements)
references
References 45 publications
23
194
3
3
Order By: Relevance
“…A fact consistent with this observation is that genome-wide screens have identified several regions that show significant linkage to AD, of which the most likely to harbor new risk factors are chromosomes 1, 9, 10, 12, 19 and 21 (Pericak-Vance et al, 1997;Rogaeva et al, 1998;Wu et al, 1998;Kehoe et al, 1999;Scott et al, 2000;Mayeux et al, 2002;Myers et al, 2002;Blacker et al, 2003;Saunders et al, 2003). Several candidate gene association studies have recently focused in examining common genetic variation among Wnt signaling components in AD.…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 76%
“…A fact consistent with this observation is that genome-wide screens have identified several regions that show significant linkage to AD, of which the most likely to harbor new risk factors are chromosomes 1, 9, 10, 12, 19 and 21 (Pericak-Vance et al, 1997;Rogaeva et al, 1998;Wu et al, 1998;Kehoe et al, 1999;Scott et al, 2000;Mayeux et al, 2002;Myers et al, 2002;Blacker et al, 2003;Saunders et al, 2003). Several candidate gene association studies have recently focused in examining common genetic variation among Wnt signaling components in AD.…”
Section: Alzheimer's Disease Apolipoprotein E and Wnt Signalingmentioning
confidence: 76%
“…Case-control studies of genetic association, while offering enhanced power, may be prone to false positive associations due to population stratification. While a number of genome scans of AD have been reported, [45][46][47][48] including one small study of AD þ P, 4 significant or suggestive linkage to chromosome 22q, where COMT is located, has not been reported. The absence of prior evidence of linkage to chromosome 22q does not exclude the possibility of association of COMT with AD þ P. We are aware of one other casecontrol study that has also found a significant association of RS4680 G alleles with psychosis risk in AD, although other SNPs were not studied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Expanded genetic study of 109 Swedish AD families A Sillén et al 6p24 region has not been reported earlier to be linked to AD, although findings of several smaller linkage peaks (LODs between 1.5 and 1.9) in the adjacent chromosomal regions 6p21 and 6q21 have been described. 14,15,17,18 In addition to the already discussed highly significant linkage to 19q13.33, the 4q25 region appeared as a suggestive peak both in the original (spt LOD ¼ 2.35, P ¼ 0.35 in the e4-positive subgroup) and this extended (spt LOD ¼ 2.31, P ¼ 0.28 in the e4-positive subgroup, and LOD ¼ 2.31, P ¼ 0.31 in 109 families) genome-wide scan for AD susceptibility genes. Although simulation analyses and the spt LOD scores of flanking markers (Supplementary Table 2) suggest that these LOD scores are not significant, one may be cautious to rule out the possibility of a susceptibility gene in this part of the genome as at least one candidate gene, COL25A1, is located in this region.…”
Section: Discussionmentioning
confidence: 99%